ChemInform Abstract: A Stereoselective Approach to Functionalized Cyclohexenones. Issue 12 (25th March 2014) - Meister, Anne C.; Sauter, Paul E.; Braese, Stefan
Abstract Short pathways towards the synthesis of highly enantio‐enriched 4‐hydroxy‐6‐methylcyclohex‐2‐enone (IV) are developed.